A Structural Model of Tenure and Specific Investments - Coen N. Teulings; Martin A. van der Ende (Tinbergen Institute, 2000)
Though a lot of work has been done on the distribution of job tenures, we are still uncertain about its main determinants.In this paper, we stress random shocks to match productivity after the start of an employment relation.The specificity of investment makes hiring and separation decisions irreversible. These decisionstherefore have an option value. Assumptions on risk neutrality, efficient bargaining, and theefficient resolution of hold up problems allow investment and separation decisions to be analyzedseparately from wage setting. The tenure profiles in wages implied by the model fit the observedpattern quite well. The model yields a hump shaped pattern in separation rates, similar to learningmodels, but with a slower decline after the peak. Estimation results using job tenure data from theNLSY support this humped shaped pattern and favor this model above the learning model. We developa methodology to analyze the decomposition of shocks to match productivity into idiosyncratic andmacro-level shocks.When assuming a Last-In-First-Out (LIFO) separation rule, this model of individual employmentrelations is embedded in a model of firm level employment, that satisfies Gibrat's law. TheLIFO rule is interpreted as an institution protecting the property rights on specific investmentsof incumbent workers against hiring new workers by the firm.
Keywords: J31; J51; 330; option value; job tenure; tenure profiles; Betriebszugehörigkeit; Arbeitsmobilität; Theorie; USA; Investition